2009
DOI: 10.1007/s12263-009-0130-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ID ACE gene polymorphism on dietary composition and obesity-related anthropometric parameters in the Czech adult population

Abstract: The aim of this study was to investigate the possible associations between insertion/deletion (ID) polymorphism in angiotensin-converting enzyme (ACE) (dbSNP rs 4646994) with the food intake and body composition in the Czech non-obese, obese and extremely obese populations. A total of 453 various-weighted individuals were enrolled in the study and were according to their BMI assigned into following subgroups, such as obese (30 B BMI \ 40), morbidly obese (BMI C40) and nonobese (20 \ BMI \ 30) subjects. Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
0
18
0
2
Order By: Relevance
“…Associations between ACE I/D and obesity parameters show the same controversy regarding the risk allele. For instance, in the study of Bienertova-Vasku et al (2009), the II-genotype was found associated with the prevalence of obesity, whereas Settin et al (2009) reported a significantly higher BMI in D-allele carriers. It has also been shown that subjects with the D/D genotype lose less body fat with similar amounts of weight loss than I-allele carriers (Hamada et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Associations between ACE I/D and obesity parameters show the same controversy regarding the risk allele. For instance, in the study of Bienertova-Vasku et al (2009), the II-genotype was found associated with the prevalence of obesity, whereas Settin et al (2009) reported a significantly higher BMI in D-allele carriers. It has also been shown that subjects with the D/D genotype lose less body fat with similar amounts of weight loss than I-allele carriers (Hamada et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that childhood overweight and obesity have increased in many developed countries [3][4][5] due to the imbalance between caloric intake and energy expenditure [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…12 However, there is also a controversial study indicating that it is not the DD-but the II-genotype that is related to the prevalence of obesity. 13 The possible explanations for such contradictory findings include the interaction with other genes or environmental factors. 5 Recently, via targeted proteomic screening, we have found that the circulating level of ACE is an important predictor of weight loss maintenance after weight loss induced by low-caloric diet (LCD) in overweight/obese female participants of the Diogenes project, 14 a pan-European dietary intervention study in overweight/obese families.…”
Section: Introductionmentioning
confidence: 99%